2017
DOI: 10.1016/j.ejmech.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

QSAR-driven design, synthesis and discovery of potent chalcone derivatives with antitubercular activity

Abstract: New anti-tuberculosis (anti-TB) drugs are urgently needed to battle drug-resistant Mycobacterium tuberculosis strains and to shorten the current 6–12-month treatment regimen. In this work, we have continued the efforts to develop chalcone-based anti-TB compounds by using an in silico design and QSAR-driven approach. Initially, we developed SAR rules and binary QSAR models using literature data for targeted design of new chalcone-like compounds with anti-TB activity. Using these models, we prioritized 33 compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 86 publications
0
48
0
1
Order By: Relevance
“…The results of the activity test indicated that compounds 1a , 1b , 1c , 1d , and 1e (Figure ) possessed minimal inhibitory concentration (MIC) of <0.33 μg/ml against rifampin‐ and isoniazid‐resistant mycobacteria. Among these compounds, compound 1b displayed the highest activity against rifampin‐resistant and isoniazid‐resistant tuberculosis bacilli and had MIC values of 0.02 and <0.01 μg/ml, respectively (Gomes et al, ).…”
Section: Five‐membered Ring Compoundsmentioning
confidence: 99%
“…The results of the activity test indicated that compounds 1a , 1b , 1c , 1d , and 1e (Figure ) possessed minimal inhibitory concentration (MIC) of <0.33 μg/ml against rifampin‐ and isoniazid‐resistant mycobacteria. Among these compounds, compound 1b displayed the highest activity against rifampin‐resistant and isoniazid‐resistant tuberculosis bacilli and had MIC values of 0.02 and <0.01 μg/ml, respectively (Gomes et al, ).…”
Section: Five‐membered Ring Compoundsmentioning
confidence: 99%
“…The availability of large datasets of chemical compounds with at least one biological property measured [25,26], associated with thousands of molecular descriptors paired with the popularization of in silico approaches resulted in the widespread use of QSAR for a diverse array of biological properties relevant to drug discovery [27][28][29][30][31][32]. However, dealing with big datasets has posed a challenge to model biological properties using classical machine learning algorithms [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to identify novel antileishmanial compounds among 32 previously synthesized chalcones and chalcone-like compounds 26 . The general workflow is shown in Figure 1.…”
mentioning
confidence: 99%
“…Amphotericin B exhibits CC 50 of 9.8 μM and SI of 5.2; therefore, LabMol-65 exhibited SI higher than the control and Labmol-73 showed selectivity index (SI) similar to or higher than the control. All active compounds were also tested against Vero cells 26 (Table 3). LabMol-65 and Labmol-73 demonstrated SI’s in the range 55–243 and 4–10, respectively, that make them promising anti-leishmanial agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation